Education Policies for Bilingualism and Stakeholders’ Views and Practices: A Multicase Study in West-Center Colombia Language Education - Jaramillo Calderón, Luis Felipe (Colombian Applied Linguistics Journal, 2025)
Bilingualism has become a major theme in language policies over the last decades, reflecting language ideologies and guidelines for practice. Yet, stakeholders have responded to these policies in diverse ways. This multi-case study explores the language and education ideologies of language policies and Colombian policy stakeholders. Specifically, it examines how stakeholders exercise their agency in the formulation and application of the policies was also explored. The data analyzed includes interviews with stakeholders (see Appendix 1)—such as policy makers, scholars, test designers, administrators of second-language teacher preparation programs and language centers, and teachers from various cities of West-Center Colombia and recent national policy documents. The study shows an emerging shift in stakeholder’s ideologies, discourses, and practices towards alternative, heteroglossic bilingual oriented views. Additionally, the study evidences the active and relevant role of stakeholders in the enactment and appropriation of policies and points to the influence stakeholders have exerted on written policies and official discourses. These findings suggest the need for more participatory and context-sensitive policies focusing on learner’s necessities, expand language curricula, and foster heteroglossic teaching and assessment practices.